Analysis of Community Socio-Economic Changes After Land Acquisition on the PT Sorik Marapi Geothermal Power Geothermal Project - Maisyaroh, Tetti; Nasution, Yenni Samri Juliati; Syahriza, Rahmi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The development of geothermal projects brings about social changes in the community environment. PT Sorik Marapi Geothermal Power's policy through the construction of this geothermal power plant also has a big impact on changes in the economic level of the local community. This research uses a qualitative research method, a phenomenological approach, trying to explain or reveal the meaning of existing concepts or experiential phenomena based on the awareness that occurs from several individuals. The results of this research show that PT Sorik Marapi Geothermal plays a big role in improving the local community's economy, including: helping the community by providing fish farming businesses, helping village income, providing scholarships to local sons/daughters, and building village infrastructure. Land acquisition for the PT Sorik Marapi Geothermal geothermal project has had an impact on the socio-economic aspects of the community, as they have lost agricultural land. However, the company provides compensation money to people who clear their land with double the profits, and no party is harmed. This is based on the basic value of Islamic economics, namely responsibility. The responsibility given by the company is to provide the greatest good (maslahah) to the community. There are two types of PT Sorik Marapi Geothermal Power, namely: First, the negative impacts that occur after land acquisition on the PT Sorik Marapi Geothermal Power geothermal project are as follows: agricultural land is decreasing, clean water supply is decreasing, noise around the project area, air pollution, the roofs of residents' houses being easily damaged, gas leaks due to company negligence, which caused fatalities. Second, the positive impact, the positive impact after land acquisition on the PT Sorik Marapi Geothermal Power geothermal project is as follows: progress in the area, increased regional income, and reduced poverty land acquisition, many people, especially in the Puncak Sorik Marapi sub-district, suddenly became rich, expanding roads around the geothermal project area and creating jobs for the surrounding community.